The Roberto Franceschi Memorial. Metaphor, structural invention and function in the mid-1970s militant culture debate (L'uomo nero. Materiali per una storia delle arti della modernità, 2023)
This contribution aims to analyse the events that led to the choice of an industrial hammer as a monument in memory of Roberto Franceschi, a militant student of Bocconi University who was killed during a demonstration in 1973. In the debate surrounding the choice of the object, contrasting cultural perspectives emerged: on one side, members of the Movimento Studentesco (Student Movement) – supported by a group of artists including Alik Cavaliere – who wanted to remember Franceschi with a realistic-inspired sculpture; on the other side, the “designers”, led by Enzo Mari, who wanted to commemorate the young student through a metaphorical representation of the values cherished by the communist and student culture of the mid-1970s: labor and education. The distance of the memorial dedicated to Franceschi from the traditional attributes of a realist-style sculpture is evident when compared with another monument dedicated in the same years to two “martyrs” of the Nuova Sinistra (New Left), the bronze stele dedicated to Giannino Zibecchi and Claudio Varalli by the sculptor Nicola Neonato.
Keywords: Enzo Mari; Alik Cavaliere; Roberto Franceschi; Nicola Neonato; Raffaele De Grada; Venice Biennial of Art